Pro iOS Table Views and Collection Views - Duckett, Tim (Apress : Imprint: Apress, 2015)
Table views and collection views are the bread and butter of iOS apps. With them, you can create everything from the simplest of lists to fully tricked-out user interfaces. Pro iOS Table and Collection Views with Swift covers table views and collection views on all sizes of iOS devices, including the new Apple Watch.